The Geometric Design of Horizontal Alignment: A Case of Bojonggede-Kemang Area Route, West Java Indonesia - Robbi Bayuaji Nugroho; Andri Irfan Rifai; Adinda Fajarika Akhir (Indonesian Journal of Multidisciplinary Science, 2022)
Roads are one of the basic infrastructure facilities in the development of an area. With the construction of roads, they can be used as access to transportation and as a driving force for an area's economy to grow better. The purpose of geometric planning on the Bojonggede-Kemang section road at STA 0 + 000 - STA 1 + 200 is to obtain a design that prioritizes user safety and comfort. The method used in this study is a manual method that refers to the 2021 Road Geometric Design Guidelines (PDGJ). The data used in this study used Google Earth. The results of the study obtained a class III primary local type road. The plan speed of 60 km / h was obtained based on the criteria design. Then, using values, the horizontal alignment of the Bojonggede-Kemang road section is of type S-C-S..